Opportunities and Challenges for New and Peripheral Political Science Communities A Consolidated Discipline? - Ilonszki, Gabriella; Roux, Christophe (Springer Nature, 2022)
This open access book offers an updated examination of the institutionalisation of political science in sixteen latecomer or peripheral countries in Europe. Its main theme is how political science as a science of democracy is influenced and how it responds to the challenges of the new millennium. The chapters, built upon a common theoretical framework of institutionalisation, are evidence-based and comparative. Overall, the book diagnoses diversity among the country cases due to their take-off points and varied political and economic trajectories.